Modulating the serine metabolism in human differentiated astrocytes: an integrated multi omics approach - Tripodi, Farida; Maffioli, Elisa; Sacchi, Silvia; Rabattoni, Valentina; Motta, Zoraide; Bearzi, Claudia; Tedeschi, Gabriella; Pollegioni, Loredano; Coccetti, Paola (Frontiers in Cellular Neuroscience, 2025)
IntroductionAstrocytes are the major source of L-serine (L-Ser) in the brain: the glycolytic intermediate D-3-phosphoglycerate is converted into L-Ser through the phosphorylated pathway (PP) made up of three enzymes, phosphoglycerate dehydrogenase (PHGDH), phosphoserine aminotransferase (PSAT) and phosphoserine phosphatase (PSP), recently proposed to generate a metabolic assembly named serinosome. In the central nervous system, L-Ser is used for a number of functions, including the synthesis of glycine (Gly) and D-serine (D-Ser), the two key NMDAR co-agonists.MethodsHere, we used iPSC-derived human astrocytes as a cellular model to evaluate the impact on cell metabolism of the overexpression of each of the three enzymes of the PP as GFP-tagged proteins.ResultsThe subcellular cytosolic localization of PP enzymes remains unchanged compared to endogenous proteins, while the complex formation is increased in all cases. Notably, among the factors involved, the overexpression of PHGDH appears to play a pivotal role in promoting the serinosome assembly and/or stabilization, highlighting the critical importance of this multi-domain protein. Particularly, the overexpression of each enzyme of the PP alters the cellular metabolism in a specific way. The L-Ser and Gly levels increase more in PHGDH overexpressing cells, in agreement with the known kinetics of the PP. A consistent increase in the TCA cycle, as well as in mitochondrial activities, serine-glycine-one carbon pathway, asparagine, arginine, purine and pyrimidines metabolism is also observed.DiscussionPeculiar alterations are observed when each enzyme of the PP is overexpressed, strongly supporting the use of human iPSC-derived astrocytes overexpressing the PP pathway enzymes as a valuable cellular model for understanding how Ser glial metabolism occurs in a non-tumor system under both physiological and pathological conditions.